An Evaluation of Sheet Mulch Made from a Combination of Hyacinth (Eichhornia crassipes (Mart.) Solms) and Musa paradisiaca L Biomass Decomposed with Either Urea or Caustic Soda - Djojowasito, Gunomo; Ahmad, Ary Mustofa; Wijaya, suri Kusuma (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
A randomized block design experiment was carried out to evaluate the quality of an organic sheet mulch made from the biomass of hyacinth (Eichhornia crassipes (Mart.) Solm) combined with banana (Musa paradisiaca L) bunch with a decomposition agent of urea or caustic soda. The hyacinth (H) and banana (B) bunch biomass were chopped and mixed at the H:B ratios of 10:0, 9:1, 8:2 and 7:3. After a further size reduction with a warring blender, the biomass mixture (600 g) was decomposed by boiling it for 30 minutes in 2 L of water added with 6 g of either urea or caustic soda. The treated biomass was then washed, dewatered by pressing and air dried to form a sheet mulch. It was found that both the normal tense and tensile strength of the sheet mulch varied with the biomass ratios and the decomposting agent. The soda treated mulch made from the biomass ratios of of 9:1 and 8:2 showed a higher normal tense and tensile strength than those treated with urea or with other biomass ratios. The yield as well as the water absorption holding capacity increased with the banana biomass. The best organic mulch sheet was obtained from the use of water hyacinth : banana bunch (8:2) treated with 1% caustic soda.Keyword: Organic Mulsa Sheet, Water Hyacinth, Banana Bunch